Prevalence rate of delirium at two hospitals in Western Australia - Speed, Gaye; Wynaden, Dianne; McGowan, Sunita; Hare, Malcolm; Landsborough, Ian (Australian Nursing Federation, 2007)
Objective: To estimate the prevalence of delirium in patients on 15 medical and surgical wards at two hospitals in Western Australia. Design: Following a review of the literature on delirium a standardised data collection tool was developed and four prevalence audits were conducted over a four week period at the target hospitals. The nurse cordinator on each ward was asked to identify any patient who was experiencing a delirium or who was confused. These patient's records were then examined for documentation that confirmed the presence of delirium or confusion. Main outcome measures: The audit measured those patients with a confirmed documented delirium and identified patients who had a possible delirium superimposed on a confirmed or suspected dementia or unconfirmed organic brain disorder. Patients with a known dementia or organic brain disorder who displayed symptoms of confusion but had no evidence of delirium were also identified. Results: Of 1209 patients surveyed in four prevalence audits, 132 patients (10.9%) displayed behaviours suggestive of the presence of delirium; however only 48 of the 132 patients had a confirmed diagnosis of delirium. The remaining 84 patients displayed features of delirium that were superimposed on symptoms of dementia (diagnosed/undiagnosed) or an organic brain disorder. An additional 51 (4.2%) of the 1209 patients were identified with confusion resulting from other causes. Conclusions: Accurate assessment of delirium is particularly important in elderly people where behaviours associated with delirium are often assumed to be caused by dementia. This may result in delirium going undiagnosed and untreated.